2012
DOI: 10.1097/jto.0b013e3182381515
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of EGFR Mutations in Korean Men Smokers with No Intratumoral Heterogeneity of Lung Adenocarcinomas: Correlation with Histologic Subtypes, EGFR/TTF-1 Expressions, and Clinical Features

Abstract: The incidence of EGFR mutations is variable according to histologic subtypes, gender, and smoking history. The mixed acinar and BAC and papillary and acinar subtypes, the presence of BAC (lepidic) or papillary components, EGFR, and TTF-1 protein expression can predict higher EGFR mutation in lung adenocarcinoma. However, intratumoral heterogeneity of EGFR mutation was not found. In addition, relatively high incidence of EGFR mutations in Korean men who smoked with adenocarcinoma histology suggests that these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
107
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(135 citation statements)
references
References 37 publications
26
107
2
Order By: Relevance
“…As GGO nodules noted at thin-section CT scan have been shown to have a histopathologic relationship with atypical adenomatous hyperplasia, BAC (or adenocarcinoma in situ), and adenocarcinoma with a predominant BAC component (minimally invasive adenocarcinoma) (Lee et al, 2011), EGFR mutation is positively correlated not only with the GGO ratio at a thin-section CT scan in lung adenocarcinomas (Lee et al, 2011), but also bronchioloalveolar pathologic subtype (Hsieh et al, 2005). Regarding histologic subtypes of adenocarcinoma, mixed acinar and BAC pattern showed the most frequent EGFR mutation (67.6%), followed by mixed papillary and acinar (65.2%), mixed solid and acinar (38.2%), micropapillary and acinar (30.4%), and acinar and mucinous BAC (13.3%) (Sun et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As GGO nodules noted at thin-section CT scan have been shown to have a histopathologic relationship with atypical adenomatous hyperplasia, BAC (or adenocarcinoma in situ), and adenocarcinoma with a predominant BAC component (minimally invasive adenocarcinoma) (Lee et al, 2011), EGFR mutation is positively correlated not only with the GGO ratio at a thin-section CT scan in lung adenocarcinomas (Lee et al, 2011), but also bronchioloalveolar pathologic subtype (Hsieh et al, 2005). Regarding histologic subtypes of adenocarcinoma, mixed acinar and BAC pattern showed the most frequent EGFR mutation (67.6%), followed by mixed papillary and acinar (65.2%), mixed solid and acinar (38.2%), micropapillary and acinar (30.4%), and acinar and mucinous BAC (13.3%) (Sun et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…If EGFR mutation status of lung cancer can be identified without molecular examination of EGFR mutation, it would be very useful for the treatment of lung cancer. Adenocarcinomas with a bronchiolo-alveolar carcinoma (BAC) component are known to be significantly correlated with EGFR mutations (Lynch et al, 2004;Pao et al, 2004;Tam et al, 2006, Sun et al, 2012. The BAC component is likely to have weak accumulation of 18F-FDG (18-fluoro-2-deoxyglucose) in positron emission tomography-computed tomography(PET-CT) ( Mori et al, 2008) and have less tissue cellularity, which is characterized by diffusionweighted magnetic resonance imaging (DWI) (Usuda et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This result is accordant with several studies that found EGFR gene mutation clusters in bronchioloalveolar carcinoma (BAC) (now classified as AIS) and that this characteristic of BAC is a predictor of response to EGFR-TKI. [23][24][25] The clinicopathological analysis revealed that higher DPD protein levels were found in females than in males and in non-smokers than in smokers. In our previous study, significantly higher DPD mRNA expression and DPD protein levels were also correlated with females and non-smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are authors that suggest that it could be left open without subsequent complication, the majority, among whom we are placed, recommend to close the muscular layer following enucleation with non-absorbable interrupted suture, in order to repair the esophageal wall and preserve the propulsive activity of the esophageal body (3,6,10,15,(19)(20)(21)26), and to avoid mucosal bulging and formation of pseudodiverticula which can cause postoperative dysphagia, which has been described by many authors. Large tumors' enucleations have been associated with muscle atrophy and large extramucosal defects, not allowing a tension-free suture, which can require tissue flaps with pleural films, diaphragm, omentum or pericardium (20).…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, other authors, among whom we are placed, recommend their excision not only in symptomatic lesions, but also in those asymptomatic sized between 1 and 5 cm, not only due to the rare possibility of malignant degeneration, but also to confirm histopathological diagnosis and differentiate them from GISTs. What also seems clear is the surgical abstention with asymptomatic tumors smaller than 1cm, because of the high difficulty to locate them in the surgical field (19)(20)(21). In such cases annual or biannual follow-up with endoscopic and/or radiologic procedures is recommended (Fig.…”
Section: Discussionmentioning
confidence: 99%